Encapsulating Sulfur Into Nickel Decorated Hollow Carbon Fibers for High-Performance Lithium-Sulfur Batteries - Yu, Dongdong; Tang, Zhihong; He, Haiyong (Frontiers in Energy Research, 2021)
Due to the high specific energy density, lithium-sulfur batteries (LSBs) have great potential in energy storage devices for electric vehicle and electronic equipment. However, poor conductivity of sulfur, large volume expansion, and lithium polysulfide dissolution limit LSBs application and promotion. In this work, graphitic hollow carbon fibers (HCF) were fabricated as a matrix to encapsulate sulfur. And nickel particles were introduced into fibers (Ni@HCF) to improve the cycle stability of sulfur cathode. On one hand, hollow structures can encapsulate sulfur and limit lithium polysulfides dissolution, and the graphitic carbon walls can provide a fast electron transport channel. On the other hand, nickel particles can accelerate the conversion of lithium polysulfides. The study results show that the initial discharge specific capacity of Ni@HCF/S cathodes reaches 1,252 mAh g−1 at the current density of 0.1C. And the capacity can be maintained at 558 mAh g−1 after 200 cycles at the current density of 1C.